2019
DOI: 10.1111/jipb.12797
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study dissects the genetic bases of salt tolerance in maize seedlings

Abstract: Excess salinity is a natural stress that causes crop yield losses worldwide. The genetic bases of maize salt tolerance remain largely unknown. Here we investigated the survival rates of 445 maize natural accessions after salt treatments. A skewed distribution of the salt‐tolerant phenotypes was observed in this population. Genome‐wide association studies (GWAS) revealed 57 loci significantly associated with salt tolerance. Forty‐nine candidate genes were detected from these loci. About 10% of these genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…A polymorphism site at a stringent threshold of P ‐value ≤0.05/n was considered to have a significant association with ETB. Haplotypes were calculated using the Haploview software (Luo et al ) and the haplotypes with shorter ETB were regarded as superior haplotypes. anova of the ETB length among haplotypes was performed using SPSS version 21.0 (IBM, USA, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A polymorphism site at a stringent threshold of P ‐value ≤0.05/n was considered to have a significant association with ETB. Haplotypes were calculated using the Haploview software (Luo et al ) and the haplotypes with shorter ETB were regarded as superior haplotypes. anova of the ETB length among haplotypes was performed using SPSS version 21.0 (IBM, USA, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Nayyeripasand et al (2019) reported a positive correlation among stress tolerance indices, including STI, SSI, and TOL, but not in the subgroups. Yu et al (2018) reported that salttolerance levels in rice (O. sativa) were not strongly correlated with rice subgroups, which was confirmed in a maize population the following year (Luo et al, 2019). Tolerance indices do not accurately distinguish cultivars under severe stress (Mardeh et al, 2006;Mohammadi, 2019), but can be used as indicators for high-yielding, salt-tolerant lines in stress, and non-stress environments or for traits like germination (Nayyeripasand et al, 2019;Sedri et al, 2019).…”
Section: Salt Stress Significantly Inhibited Seed Germinationmentioning
confidence: 98%
“…mays) is a glycophytic specie that is sensitive to saline-alkaline stress 29 . Previous studies have shown that natural maize inbred lines show large variations of sensitivity to saline and saline-alkaline stress, and which is substantially attributed to the variations of shoot Na + contents 30,31 . Here, we show that a calcium-binding EF-hand protein ZmNSA1 underlies the natural variations of shoot-Na + contents under NaHCO 3 condition by a GWAS analysis.…”
mentioning
confidence: 99%